Ruchy społeczne i myśl polityczna – co, jak i po co badać? - Malendowicz, Paweł (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
The article is a form of reflection upon the research subject, the research methods and the aim of research on social movements and political thought. The author of the article suggests that in the research being carried out one should use methods characteristic of other scientific disciplines and the terms used in other sciences, for example in medicine, cognitive science or sociology. Replying to the question of the aim of research, the author explains that science is to serve the cognition and understanding of the world. Science is not supposed to be an art cultivated by a small circle of scholars in order not to contribute to the degeneration of the social system.
Social movements and political thought – what, how and why to research?
Keywords: science; academic research; the aim of research; social movement; political thought